Resistance Mapping of the Genus Cyperus in Rio Grande do Sul and Selection Pressure Analysis - ULGUIM,A.R. (2019)
ABSTRACT: Among the species of the genus Cyperus occurring in paddy rice, C. esculentus, C. difformis and C. iria are the most important, and the latter two are reported as resistant to herbicides in Rio Grande do Sul (RS). The aim of this work was to characterize and mapping the occurrence of resistant plants of the genus Cyperus in areas of paddy rice in RS State, and to analyze the agronomic factors that interfere in the resistance selection. Seeds from individual plants were harvested in the 2014/15 crop, characterized as control failures by the application of acetolactate synthase inhibitors (ALS), totaling 43 samples. At the time of collection, the grower was inquired on aspects related to the management of weeds in the crop. Seeds were germinated in BOD and when seedlings were in two leaves stage they were transplanted into 0.3 L pots containing substrate. When the plants had 4-6 leaves, imazapyr + imazapic was spray at the registration rate. Thirty days after application, control of the tested biotypes was evaluated, converting the data to binary scale, where zero (0) and one (1) correspond to susceptibility and resistance, respectively. The agronomic factors that denote the high selection pressure of resistant biotypes are the consecutive use of Clearfield® technology, the use of higher doses than the registration and the low crop rotation adoption. Although not mentioned as one of the main weeds, it is observed that almost half of the samples collected from plants of the genus Cyperus are resistant to the ALS inhibitors, distributed in almost all the growing regions.